PENERAPAN INSPEKSI PIPA SEBAGAI SALAH SATU PREVENTIVE SAFEGUARD DALAM KESELAMATAN PROSES - Maslina, Maslina; Mastrilianto, Sidik; Hanafi, Hanafi (IDENTIFIKASI, 2021)
Process Safety is a branch of the science of safety that focuses on special accident control and characteristic of the process industry. Process Safety focuses on preventing the acute release of energy or substance in harmful quantities and limiting the magnitude and consequences of the discharge event. Process Safety can be achieved by reducing hazards and risks incurred at a wide acceptable level by the organization and / or society (Marshall and Ruhemann (IIPS), 2007). One such release is the Loss of Primary Containment (LOPC) which according to the American Petroleum Institute Recommended Practice (API RP) 754 is the release of flammable, toxic, corrosive, reactive, thermal, and pressure material from primary containment which includes: tanks, pressure vessels, pipes, trucks, rail cars, or equipment as primary containers or used for processing with the potential to cause damage. In the American Petroleum Institute Recommended Practice (API RP) 750 elements of Assuring The Quality and Mechanical Integrity of Critical Equipment that pressure vessels, machines and pipes shall be designed, manufactured, installed and maintained or inspected in accordance with required requirements. One form of corporate risk management is to conduct inspections as one of the Preventive Safeguards in Process Safety to prevent Loss of Primary Containment (LOPC). Keywords: Implementation of Inspection, Preventive Safeguard, Process Safety